"Bring your own device opportunities", challenges and risks in organizations - Moreno Rojas, David Leonardo (2015)
The current availability of 3G services, 4G and growth presented by mobile technology in devices such as smartphones, tablets and laptops have spawned a new phenomenon in organizations which integrates communication and the ability to conduct business from their own devices . BYOD (Bring Your Own Device), means that employees can use their personal devices to access resources within the organization and outside it in order to do their job, this represents new opportunities, but also involves mitigating and assume the risks that are associated. This article presents opportunities, challenges and risks that may arise in organizations when they allow access to the corporate network of personal devices for employees to carry out their activities.